The Implications of Educational and Methodological Background for The Career Success of Nobel Laureates: Looking at Major Awards - Ho Fai Chan; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2013)
Nobel laureates have achieved the highest recognition in academia, reaching the boundaries of human knowledge and understanding. Owing to past research, we have a good understanding of the career patterns behind their performance. Yet, we have only limited understanding of the factors driving their recognition with respect to major institutionalized scientific honours. We therefore look at the award life cycle achievements of the 1901 to 2000 Nobel laureates in physics, chemistry and physiology or medicine. The results show that Nobelists with a theoretical orientation are achieving more awards than laureates with an empirical orientation. Moreover, it seems their educational background shapes their future recognition. Researchers educated in Great Britain and the US tend to generate more awards than other Nobelists although there are career pattern differences. Among those, laureates educated at Cambridge or Harvard are more successful in Chemistry, those from Columbia and Cambridge excel in Physics, while Columbia educated laureates dominate in Physiology or Medicine.
Keywords: M52; J33; Z13; 330; Nobel Prize; Nobel Laureates; Awards; Recognition; Educational Background; Theory; Empirics; Chemistry; Physics; Physiology or Medicine